Microbial methane production from calcium carbonate at moderately alkaline pH - Nicole A. Fiore; Anthony J. Kohtz; Daniel N. Miller; Sanjay Antony-Babu; Donald Pan; Caitlin Lahey; Xi Huang; Yongfeng Lu; Nicole R. Buan; Karrie A. Weber (Communications Earth & Environment)
Abstract Carbonate minerals are considered a metastable carbon reservoir under alkaline conditions. Here we demonstrate calcium carbonate as a sole inorganic carbon source at moderately alkaline pH for a methanogenic microbial community enriched from alkaline, saline wetland soil. In reactors amended with calcium carbonate as the sole source of inorganic carbon, concentrations of methane and aqueous calcium increased concurrent with headspace hydrogen depletion. Cells were observed in association with the carbonate mineral matrix via coherent anti-Stokes Raman scattering and two-photon excitation fluorescence microscopy. Genome-resolved metagenomics of the enrichment community confirmed the presence of a methanogen (Methanobacterium sp.) with the metabolic potential for hydrogenotrophic methanogenesis in addition to five bacterial community members. These results demonstrate that carbonate minerals can serve as an inorganic carbon source for hydrogenotrophic methanogenesis, leading to mineral dissolution under stable alkaline conditions. As such, hydrogenotrophic methanogens may impact carbon biogeochemistry and carbonate mineral stability in environmental systems.